EFFECT OF YEAST TYPE ON ANTIOXIDANT ACTIVITY AND PHENOLIC CONTENT IN FERMENTED TALIPUK SEED FLOUR - Titis Linangsari; Ema Lestari; Dwi Sandri (BPFP Faperta UNIB, 2022)
Talipuk seed flour is processed from mature talipuk seeds. This flour is commonly used as a raw material for traditional cakes and as a substitute for wheat flour by the people of South Kalimantan. Talipuk seeds contain various compounds that function well for health. However, talipuk seeds are less desirable because they have a sandy texture and contain anti-nutritional compounds that cause a less desirable flavor. This can be overcome by fermentation by yeast. This study was conducted to analyze the functional properties (total phenolic content by the Folin-Ciocalteau method and antioxidant activity with the free radical inhibitor DPPH (2,2-diphenyl-1-picrylhydrazil) in talipuk seed flour fermented with various yeasts. Talipuk seeds were fermented by fermentation spontaneously, tape yeast, baker's yeast and tempeh yeast for 48 hours. The results of the fermentation are dried using an oven at 60oC for 8 hours or with a hot sun for ± 12 hours. Then mashed and sieved with a 60 mesh flour sieve to obtain fermented talipuk seed flour Based on the results of research, the fermentation of talipuk seed flour can increase the total phenolic content and antioxidant activity of talipuk seed flour. The highest total phenolic in the fermentation of talipuk seed flour using baker's yeast is 61.22 mg/g GAE and tape yeast 56.40 mg/g GAE, while the highest antioxidant activity in unfermented talipuk bij flour was 84.85%, followed by fermentation of talipuk seed flour using 47.34% baker's yeast and 36.34 % tape yeast. The use of baker's yeast and tape yeast in the fermentation of talipuk seed flour gave better total phenolic and antioxidant activity test results than spontaneous fermentation and fermentation using tempeh yeast.